2008
DOI: 10.1101/gad.475808
|View full text |Cite
|
Sign up to set email alerts
|

Inverse regulatory coordination of motility and curli-mediated adhesion in Escherichia coli

Abstract: S produces a fine-tuned checkpoint system that "unlocks" curli expression only after down-regulation of flagellar gene expression. In summary, these data reveal the logic and sequence of molecular events underlying the motile-to-adhesive "lifestyle" switch in E. coli.[Keywords: Adhesion; c-di-GMP; flagella; GGDEF; EAL; RpoS] Supplemental material is available at http://www.genesdev.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
451
0
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 318 publications
(491 citation statements)
references
References 54 publications
(81 reference statements)
28
451
0
3
Order By: Relevance
“…c-di-GMP intracellular concentrations did not strictly correlate with DGC overproduction levels, as judged by SDS-PAGE analysis of cell extracts (data not shown). The expression of each DGC led to a reduction in bacterial mobility (Supplementary Table S2), in agreement with earlier observations (Méndez-Ortiz et al, 2006;Jonas et al, 2008;Pesavento et al, 2008).…”
Section: Overexpression Of Dgcssupporting
confidence: 81%
See 2 more Smart Citations
“…c-di-GMP intracellular concentrations did not strictly correlate with DGC overproduction levels, as judged by SDS-PAGE analysis of cell extracts (data not shown). The expression of each DGC led to a reduction in bacterial mobility (Supplementary Table S2), in agreement with earlier observations (Méndez-Ortiz et al, 2006;Jonas et al, 2008;Pesavento et al, 2008).…”
Section: Overexpression Of Dgcssupporting
confidence: 81%
“…In Enterobacteria, biosynthesis of the c-di-GMP signal molecule by DGCs stimulates the transition from planktonic to biofilm cells, repressing flagellar synthesis and cell motility, while promoting production of adhesion factors (Méndez-Ortiz et al, 2006;Pesavento et al, 2008). In this report, we have shown that overexpression of YddV, a DGC protein, promotes production of the EPS PNAG (Figs 2 and 3) by activating the expression of pgaABCD, the PNAG biosynthetic operon (Fig.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…For instance in Escherichia coli, CsgD is a key transcriptional regulator for curli production as well as a master regulator of biofilm formation. CsgD was shown to directly repress gene expression of flagella components, and activate the synthesis of extracellular polysaccharides, thereby switching from planktonic growth to the biofilm mode (Zogaj et al, 2001;Pesavento et al, 2008). Moreover, CsgD modulates adrA upregulation, which encodes one of the enzymes for cyclic di-GMP synthesis (Ogasawara et al, 2010).…”
Section: Regulation Of Crenarchaeal Biofilm Formationmentioning
confidence: 99%
“…The fliZ gene, which is co-transcribed with fliA, encodes a protein which acts as a positive regulator of motility, and as an inhibitor of the expression of curli fimbriae, which are required for surface-attached growth (Pesavento et al, 2008;Saini et al, 2008). The fliLMNOPQR operon encodes structural components of the flagellum and the flagellin export apparatus (Chilcott and Hughes, 2000).…”
mentioning
confidence: 99%